ANALYSIS OF INTENT-DESIGN RELATIONSHIP FOR ARTIFICIAL INTELLIGENCE DESIGN AGENT MODEL BASED ON PRODUCT PURCHASING PROCESS. (May 2020) - Le, M.; Jung, E.-C.
Abstract: This study aims at proposing an AI-agent model that helps designers to understand and interpret clients' intent and create customized design outcomes. We recorded and analysed the purchasing process of collecting product information, selecting alternative products and making decision to understand the influence of artefacts on the client's intent during the purchasing process and collect the basic data for proposing an AI-agent model. We analysed the process by Linkography and found the relationship between the decision-making patterns and the artefacts that presented by the AI-agent.